PENGARUH NILAI BUDAYA DALAM NOVEL YANG BERJUDUL “TENGGELAMNYA KAPAL VAN DER WIJCK” TERHADAP PEMBELAJARAN BAHASA INDONESIA - Fauziah, Fauziah; Nugraha, Fajar; Zenab, Ai Siti (IKIP Siliwangi, 2019)
The novel is a literary work in the form of prose. There are many titles novel that has been print, one of them novel sinking Van der Wijk. Novel research novel tengelamnya ship Van der Wijk aims to describe the story of the novel is may affect the reader students SMPN 1 padalarang. This research was performed using the qualitative methods and techniques research include the stage of data collection, data analysis, the presentation of the data and withdrawal conclusion. Source of data obtained the form of the primary data (tengelamnya ship Van der wijck) and secondary from other sources. Research has a crucial role in providing feedback to readers. From the results showed that the aspects of educational value sinking Van der wijcksebanyak 57.3%, this indicates that readers novel sinking Van der Wijk give appreciation to refer to the contents of the story very reasonable. The second aspect of the figure of figures tengelamnya ship Van der wijck with the result is 50,6% indicating that the respondents average like to figure novel sinking Van der wijck, while aspects of the third called aspect of the events that occurred with the result are 40.66%. Of the three aspects can be concluded that the novel sinking Van der Wijk quite interesting.